A prototype of traffic tally counter evaluation system using pocket PC approach and Microsoft Visual basic.net / Mohd Ismail Mohd Aripin - Mohd Aripin, Mohd Ismail (Faculty of Information Technology and Quantitative Sciences, 2005)
The main purpose of a Personal Digital Assistant (PDA) is to act as an electronic organizer or day planner that is portable, easy to use and capable of sharing information with a Personal Computer (PC). It's supposed to be an extension of the PC, not a replacement. The traditional PDAs are actually descendents of the original Palm Pilot and Microsoft's Handheld PC devices. Pocket PC is the generic name for Windows Mobile PDAs. The scope of the project is to develop a prototype of a Pocket PC application and Windows based system that will be used as a traffic counter and evaluation program. Prototyping technique was chosen for this project because a prototype is an initial version of software system which is used to demonstrate concepts, try out design options and generally it is easier to come up with probable solutions and problem identification. Prototyping involves a repetitive sequence of Analysis, Design, Modeling and Testing. Prototyping allows users to examine a model that accurately represent system outputs, inputs, interfaces and processes. Decision on what development tools to use is very important because there many other programming tools or language available in the market. A study on various languages and tools must be done in order to find out the advantages and disadvantages of each programming language and tool. It is also important to ensure that the process of studying these languages and tools, developing the system must not exceed the given period.